Understanding engineering ethics - Shuriye, Abdi Omar (IIUM Press, 2011)
Engineering ethics aims to enhance engineer’s ability to confront moral issues raised by engineering activities. It covers engineering as social experimentation, the engineer’s responsibility for safety, and the rights of engineers. What constitutes engineering ethics is the underlining question of this research. Hence, the objective of the research is to systematically provide answers to the aforementioned question. The research also studies the scope and the origin of the subject matter. At the same time, the research highlights the significance of the subject from diverse perspectives; including Western and Islamic perspectives.